Branded with the same mobility brush – the construction workforce in the Australian resources industries. (1st October 2020) - Haslam McKenzie, Fiona M.
ABSTRACT: The construction workforce and its relationship with the resources industries is an under-researched sector of the mobile labour market. While it is broadly assumed that the construction workforce is an integral part of the resources industry, those with a familiarity with resource boomtowns perceive the construction workforce to be different or 'other', mostly viewing the workers to be socially, economically and culturally inferior with different values, practices and rewards. The 'new mobilities paradigm' and Employment-Related Geographical Mobility provide useful frameworks to examine the nuances of mobile workers, placing mobility at the centre of an assessment of paid work and socio-economic differentiation in Western Australian resources boomtown settings. The lived experience of construction workers and their families are interrogated providing an insight into the complex and unequal 'relatedness' of the sector to the resources industries, another sector employing a mobile workforce.